Ocean change within shoreline communities: from biomechanics to behaviour and beyond. Issue 1 (18th November 2019) - Gaylord, Brian; Barclay, Kristina M; Jellison, Brittany M; Jurgens, Laura J; Ninokawa, Aaron T; Rivest, Emily B; Leighton, Lindsey R
Abstract: Humans are changing the physical properties of Earth. In marine systems, elevated carbon dioxide concentrations are driving notable shifts in temperature and seawater chemistry. Here, we consider consequences of such perturbations for organism biomechanics and linkages amongst species within communities. In particular, we examine case examples of altered morphologies and material properties, disrupted consumer–prey behaviours, and the potential for modulated positive (i.e. facilitative) interactions amongst taxa, as incurred through increasing ocean acidity and rising temperatures. We focus on intertidal rocky shores of temperate seas as model systems, acknowledging the longstanding role of these communities in deciphering ecological principles. Our survey illustrates the broad capacity for biomechanical and behavioural shifts in organisms to influence the ecology of a transforming world. Abstract : Lay Summary : Brief overview of biomechanical and behavioural consequences of ocean acidification and warming for marine organisms and communities inhabiting rocky temperate shores.